Geochemistry and petrogenesis of Late Carboniferous igneous rocks from southern Mongolia: Implications for the post-collisional extension in the southeastern Central Asian Orogenic Belt. (15th August 2017) - Hu, Chuansheng; Li, Wenbo; Huang, Qiuyue; Xu, Cheng; Zhou, Jiaan; Li, Zhihua
Graphical abstract: Highlights: The diabase dykes and porphyritic granites simultaneously formed at 306 Ma. The quartz monzonites formed at 300 Ma. All the Late Carboniferous mafic to felsic rocks formed in a post-collisional extensional setting. Abstract: Late Carboniferous is a critical period in terms of the tectonic evolution of the Central Asian Orogenic Belt (CAOB). In this study, we report the petrology, geochronology and geochemistry of Late Carboniferous mafic to felsic rocks from southern Mongolia, to better characterize the Late Carboniferous magmatism in the southeastern CAOB. Three types of igneous rocks have been identified, including diabase dykes, porphyritic granites and quartz monzonite dykes. LA-ICP MS zircon U-Pb dating of these rocks shows that the diabase dykes and porphyritic granites were simultaneously emplaced at 306 Ma. The quartz monzonite dykes were subsequently emplaced at 300 Ma. The diabases belong to the high-K calc-alkaline series and show strong enrichment of large ion lithophile elements (LILE; e.g., Rb, Ba and Sr) and depletion in high field strength elements (HFSE; Nb, Ta and Ti), with enriched mantle isotopic signature (εNd (t) = −2.6 to +0.5). They were likely derived from the partial melting of metasomatized sub-continental lithospheric mantle (SCLM) and experienced variable degrees of crustal contamination. The porphyritic granites are characterized by high SiO2 contents, strong negative Eu anomalies with low εNd (t) values of −3.0 to −2.7, suggesting that they were derived from crustal anatexis and experienced strong fractional crystallization. Compared with the porphyritic granites, quartz monzonites display lower SiO2 contents, weaker negative Eu anomalies with higher and more variable εNd (t) values (−0.3 to +4.2). This indicates that the quartz monzonites were probably generated by the mixing of crust- and mantle-derived magmas. The petrographic and geochemical data suggest that all the mafic to felsic rocks in the southern Mongolia formed in a post-collisional extensional setting.